Application of repetitive transcranial magnetic stimulation in lower limb rehabilitation after stroke - LI Yajie; XING Zheng; CHU Xiaolei; LI Qi (Yixue xinzhi zazhi)
Stroke is an important factor causing disability and death worldwide, and post-stroke hemiplegia is the main clinical symptom of patients. Lower limb motor dysfunction is one of the most common complications, seriously affecting patients' walking ability and daily living activities, and bringing huge burden to social economy and personal health. How to effectively promote the rehabilitation of lower limb function in stroke patients is a challenge that needs to be addressed in clinical rehabilitation. Repetitive transcranial magnetic stimulation (rTMS), as a non-invasive and painless neural regulation technique, has become a new supplementary method for improving limb dysfunction in stroke patients in recent years. It has been widely used to recover post-stroke motor dysfunction and has achieved good results. This review mainly summarized the application of TMS, rTMS and their different stimulation modes, bilateral brain rTMS, and individnalized targeted TMS in lower limb rehabilitation of stroke patients, to provide reference for related research and clinical applications.